Hatch Success and Recruitment Patterns of the Bog Turtle. Issue 2 (23rd December 2020) - Knoerr, Michael D.; Graeter, Gabrielle J.; Barrett, Kyle
ABSTRACT: Researchers suggest that several bog turtle ( Glyptemys muhlenbergii ) populations in North Carolina, USA, are in decline and have few remaining individuals and low annual survival probability. Most populations are dominated by older adults with few juveniles encountered; however, the proportion of juveniles encountered in 2 populations is higher. It is unknown why the juvenile:adult ratio varies among populations. We conducted a nest monitoring study in 2016 and 2017 to test the hypothesis that sites with fewer juvenile encounters would be where nest predation was highest. We documented the fate of 272 eggs from 83 nests encountered across 7 sites in North Carolina. On average 28% of eggs hatched across all sites over both years, but we observed large variation in hatch success among sites. Predation by mesopredators and small mammals was the primary cause of nest failure. The probability of nest predation decreased with greater emergent vegetation density and increased with greater distance to the edge of the wetland. Cooler temperatures, which prolonged incubation and thus increased predation risk, may also hinder recruitment at higher elevation sites. Our observations are consistent with the hypothesis that nest predation would be highest at sites with fewer juvenile encounters. Managers concerned about low bog turtle recruitment rates should consider the role of nest predation and the potential benefits of management that increases hatch rates. © 2020 The Wildlife Society. Abstract : Variation in nest predation mirrors variation in recruitment patterns observed in bog turtle populations in western North Carolina, USA, 2016–2017. Mesopredators and small mammals depredated bog turtle nests and the probability of nest predation was affected by vegetation condition and distance to the edge of the wetland. Cooler temperatures may also hinder recruitment at higher elevation sites.